(100) GaAs surface treatment prior to contact metal deposition in AlGaAs/GaAs quantum cascade laser processing - Papis, Ewa; Barańska, Anna; Karbownik, Piotr; Szerling, Anna; Wójcik-Jedlińska, Anna; Bugajski, Maciej; Rzodkiewicz, Witold; Szade, Jacek; Wawro, Andrzej (Oficyna Wydawnicza Politechniki Wrocławskiej, 2009)
The effects of HCl-based chemical and Ar+ sputter etching treatment on (100) GaAs surface properties with the aim to develop the procedure of surface preparation before metal deposition have been investigated. Variable angle spectroscopic ellipsometry, X-ray photoelectron spectroscopy, atomic force microscopy and photoluminescence have been used to study the surface characterization. We show that combining chemical etching in 5% HCl with Ar+ sputter etching gives the best results for surface cleaning prior to metal deposition. The application of this two-step treatment allows to obtain Ni/AuGe/Ni/Au ohmic contact with rc = 2×10–6 Ωcm2 with excellent adhesion and long-term thermal stability.
Optica Applicata, Vol. 39, 2009, nr 4, s. 787-797
Keywords: optyka; GaAs; surface treatment; sputter etching